2015
DOI: 10.1099/ijs.0.000220
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus petrasii subsp. pragensis subsp. nov., occurring in human clinical material

Abstract: Seven coagulase-negative, oxidase-negative and novobiocin-susceptible staphylococci assigned tentatively as Staphylococcus petrasii were investigated in this study in order to elucidate their taxonomic position. All strains were initially shown to form a genetically homogeneous group separated from remaining species of the genus Staphylococcus by using a repetitive sequence-based PCR fingerprinting with the (GTG)(5) primer. Phylogenetic analysis based on 16S rRNA gene, hsp60, rpoB, dnaJ, gap and tuf sequences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…The description is the same as for Staphylococcus petrasii subsp. pragensis [57]. The DNA G+C content (mol%) of the type strain genome is 33.1 %, its approximate genome size is 2.45 Mbp, its GenBank accession is GCA_004785665.1.…”
Section: Description Of Staphylococcus Pragensis Sp Novmentioning
confidence: 99%
“…The description is the same as for Staphylococcus petrasii subsp. pragensis [57]. The DNA G+C content (mol%) of the type strain genome is 33.1 %, its approximate genome size is 2.45 Mbp, its GenBank accession is GCA_004785665.1.…”
Section: Description Of Staphylococcus Pragensis Sp Novmentioning
confidence: 99%
“…Subspecies jettensis was recovered from wounds and implicated in bacteremia, whereas subspecies pragensis is believed to have caused prostatitis (23)(24)(25). One new species of coagulase-positive Staphylococcus, Staphylococcus argenteus, was isolated from the blood of a person in Australia.…”
Section: Gram-positive Coccimentioning
confidence: 99%
“…For each of the top 10 most influential genera ( Table 1 ), the OTU that had the highest abundance in each genus bin was searched with MegaBLAST ( Morgulis et al, 2008 ) for highly similar sequences within the 16S rRNA sequence database from NCBI. For each sequence searched by MegaBLAST, the most highly similar sequence with information on source was summarized: genera found more frequently in Golden were associated with soil, horse dung, airborne dust, hard water, and clinical isolates ( Busse, 2003 ; Gallego, 2006 ; Kampfer, 2006 ; Muurholm et al, 2007 ; Smet et al, 2014 ); genera common to Sunshine are reported in swimming pool water, clinical material, cultivated land, and may be spore forming ( An et al, 2007 ; Furuhata et al, 2013 ; Amend et al, 2015 ; Echahidi et al, 2015 ; Im et al, 2015 ). Though Adonis showed no significant difference between samples with different storm-origins via the weighted Unifrac distance, there are obvious taxonomic differences between storm trajectories ( Fig.…”
Section: Resultsmentioning
confidence: 99%